Gambaran Kelelahan Mata Pada Pekerja Bengkel Las - Novianus, Cornelis (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Eye fatigue is a symptom caused by excessive exertion of the visual system when under suboptimal conditions to achieve visual acuity. Welders are highly exposed to ultraviolet (UV) radiation, which can affect eye function. The aim of this study is to description of eye fatigue in welding workshop workers. This research uses a descriptive quantitative method with a sample size of 65 workers, selected using the total sampling technique. The results showed that 81.5% of welding workers experienced eye fatigue; 81.5% were exposed to welding for more than 5 hours; 80% did not use personal protective equipment (PPE); 63.1% welded at a distance of less than 52 cm; and 60% were exposed to high levels of UV radiation. It is recommended that welding workers consistently use appropriate ppe and take short eye breaks of 10–15 minutes per hour to reduce eye fatigue. Workshop owners are also encouraged to provide ppe that is suitable for the hazards present in welding activities.